Implementation of the Basic Principles of Sharia Insurance at PT. Prudential Syariah Binjai Branch - Siska Junianti Br Perangin-angin; Fauzi Arif Lubis (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
PT. Prudential Sharia Branch Binjai is an Indonesia insurance company whose mission is to provide future welfare and health through varios product,including life and health insurance.The purpose of this study is to determine the basic principles of sharia insurance at PT. Prudential Sharia Binjai Branch.The qualitative research methodology used in this final theree includes surveys and interviews.Sharia insurance is an insurance is an insurance system based on islamic sharia in its service process and operation.Sharia comes from the provisions in the Qur’an ans as-sunnah.The emergence of sharia insurance in the Islamic world is based on the assumption that insurance states that existing insurance so far,namely convensional insurance contains many element: gharar,maisir,usury.This shariainsurance has principle that are firmly held,namely ta’awumu ‘ala al-birr wa al-taqwa (please help all of you in goodness and piety) and al-ta’min (feel of security).